2017
DOI: 10.5624/isd.2017.47.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the reconstruction filter in cone-beam CT to improve periodontal ligament space visualization: An in vitro study

Abstract: PurposeEvaluation of alveolar bone is important in the diagnosis of dental diseases. The periodontal ligament space is difficult to clearly depict in cone-beam computed tomography images because the reconstruction filter conditions during image processing cause image blurring, resulting in decreased spatial resolution. We examined different reconstruction filters to assess their ability to improve spatial resolution and allow for a clearer visualization of the periodontal ligament space.Materials and MethodsCo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The irregular morphology of the PDL in artificial phantoms and the filling of the PDL space with water might have caused this result. Authors found that a development filter improved the partial resolution and allowed for better measurement of the PDL space (15). In our study, the CBCT images were sharp and the number of PDL spaces with clearer boundaries were high and built-in enhancement tools were used when deemed necessary.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…The irregular morphology of the PDL in artificial phantoms and the filling of the PDL space with water might have caused this result. Authors found that a development filter improved the partial resolution and allowed for better measurement of the PDL space (15). In our study, the CBCT images were sharp and the number of PDL spaces with clearer boundaries were high and built-in enhancement tools were used when deemed necessary.…”
mentioning
confidence: 68%
“…Another study reported a natural PDL space width of 0.14-0.24 mm (23). Studies evaluating the visualisation of the PDL have generally developed in vitro phantom models to simulate the PDL cavity and surrounding tissues (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations